2017
DOI: 10.1016/j.rmcr.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Erdheim-Chester disease, moving away from the orphan diseases: A case report

Abstract: With approximately 750 cases reported, Erdheim-Chester disease is an exceedingly rare histiocyte cell disorder. Affected sites typically include long bones, large vessels and central nervous system. However, cutaneous and pulmonary involvement can also occur. The diagnosis is ascertained by identification of foamy histiocytes positive for CD68, CD163, and factor XIIIa on immunoperoxidase staining. Recently published literature have described an association between Erdheim-Chester disease and BRAF V600E mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The study found that the sensitivity of [18]F-FDG PET/CT with respect to CT/MRI varied widely among organ systems, but that [18]F-FDG PET/CT was nearly 100% specific. Our study was different from this study in that [1] we did not assume that either modality was the gold standard, and also [2] we compared PET to CT outside of the nervous system where the prior study used MRI in other instances. Overall, we do not find our results at odds with this study, although our study highlights the possibility that [18]F-FDG PET/CT can detect lesions not seen on CT and therefore is of diagnostic value in the initial ECD evaluation.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The study found that the sensitivity of [18]F-FDG PET/CT with respect to CT/MRI varied widely among organ systems, but that [18]F-FDG PET/CT was nearly 100% specific. Our study was different from this study in that [1] we did not assume that either modality was the gold standard, and also [2] we compared PET to CT outside of the nervous system where the prior study used MRI in other instances. Overall, we do not find our results at odds with this study, although our study highlights the possibility that [18]F-FDG PET/CT can detect lesions not seen on CT and therefore is of diagnostic value in the initial ECD evaluation.…”
Section: Discussionmentioning
confidence: 83%
“…18 F-FDG PET/CT of the body was reviewed for all patients, and dedicated 18 F-FDG PET/CTs of the brain were reviewed when available. The organ systems reviewed were [1] intracranial, [2] craniofacial, [3] spinal, [4] pulmonary, [5] cardiovascular, [6] GI tract, [7], reproductive, [8] osseous, [9] skin and subcutaneous soft tissues, [10] lymph nodes and other soft tissues, and [11] other sites of disease otherwise not in the above categories.…”
Section: [18]f-fdg Pet/ct Imaging and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, around 750 cases of ECD have been reported in literature (including around 500 cases in English literature in a PubMed search) [8,9]. Involvement of the extracranial head and neck region has been reported sparsely, with all of these cases being a part of systemic illness.…”
Section: Introductionmentioning
confidence: 99%
“…The renal involvement seen in this image (Figure) displays a unique "hairy kidney" appearance commonly associated with Erdheim-Chester disease (ECD), 1 an extremely rare condition with approximately 750 reported cases in literature. 2 Erdheim-Chester disease is a none Langerhans cell histiocytosis characterized by the infiltration of foamy histiocytes with fibrosis that can affect many organs, most commonly long bones. 3 Renal involvement commonly manifests in this disease as a histiocytic infiltration into the perirenal fat (arrows).…”
mentioning
confidence: 99%